EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) DAN THINK PAIR SHARE (TPS) PADA POKOK BAHASAN PERSAMAAN DAN PERTIDAKSAMAAN KUADRAT DITINJAU DARI GAYA BELAJAR SISWA KELAS X SMA SE KABUPATEN SUKOHARJO TAHUN PELAJARAN 2015/2016 - Herawati, Ratna; Budiyono, Budiyono; Usodo, Budi (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The aim of this research was to know the effect of learning models on mathematics achievement viewed from the learning style. The learning models compared were Group Investigation, Think Pair Share, and Direct Learning Model (GI, TPS, langsung). This research was a quasi experimental with the factorial design of 3Ã3. The population of this research was all of students in firstâgrade of Senior High Schools of Sukoharjo regency in academic year 2015/2016. The samples of the research consisted of 269 students and were gathered through stratified cluster random sampling. The instruments consisted of pre-experiment test, test of learning achievement and learning style questionnaire. Hypothesis testing was performed using two-way analysis of variance with unbalanced cells. Based on the results of hypotheses testing, they were concluded as follows. 1) GI and TPS learning models gave an equal mathematics achievement. GI learning models gave mathematics achievement better than Direct Learning Model. TPS and Direct learning models gave the same mathematics achievement. 2) Students with visual learning style have better mathematics achievement than students with auditory and kinesthetic ones. On the other hand, students with auditory and kinesthetic learning style have equal mathematics learning achievement. 3) On all visual, auditory and kinesthetic learning style, cooperative learning with GI type gives an equalsâmathematics learning achievement with TPS. GI learning models gave mathematics achievement better than Direct Learning Model. Also TPS and Direct learning models gave the same mathematics achievement. 4) On all learning models, cooperative learning GI type, TPS, and Direct Learning Model, Students with visual learning style have better mathematics achievement than students with auditory and kinesthetic ones. On the other hand, students with auditory and kinesthetic learning style have equal mathematics learning achievement.Keywords: Group Investigation, Think Pair Share, Learning Style, Mathematics Learning Achievement.Â